Powder-XRD and (14) N magic angle-spinning solid-state NMR spectroscopy of some metal nitrides - Kempgens, Pierre (Magnetic resonance in chemistry : MRC, 2016)
Copyright © 2015 John Wiley & Sons, Ltd.